First results of a simultaneous measurement of tritium and 14C in an ultra-low-background proportional counter for environmental sources of methane. (May 2016) - Mace, E.K.; Aalseth, C.E.; Day, A.R.; Hoppe, E.W.; Keillor, M.E.; Moran, J.J.; Panisko, M.E.; Seifert, A.; Tatishvili, G.; Williams, R.M.
Abstract: Simultaneous measurement of tritium and 14 C would provide an added tool for tracing organic compounds through environmental systems and is possible via beta energy spectroscopy of sample-derived methane in internal-source gas proportional counters. Since the mid-1960's atmospheric tritium and 14 C have fallen dramatically as the isotopic injections from aboveground nuclear testing have been diluted into the ocean and biosphere. In this work, the feasibility of simultaneous tritium and 14 C measurements via proportional counters is revisited in light of significant changes in both the atmospheric and biosphere isotopics and the development of new ultra-low-background gas proportional counting capabilities for small samples (roughly 50 cc methane). A Geant4 Monte Carlo model of a Pacific Northwest National Laboratory (PNNL) proportional counter response to tritium and 14 C is used to analyze small samples of two different methane sources to illustrate the range of applicability of contemporary simultaneous measurements and their limitations. Because the two methane sources examined were not sample size limited, we could compare the small-sample measurements performed at PNNL with analysis of larger samples performed at a commercial laboratory. These first results show that the dual-isotope simultaneous measurement is well matched for methane samples that are atmospheric or have an elevated source of tritium (i.e. landfill gas). However, for samples with low/modern tritium isotopics (rainwater), commercial separation and counting is a better fit. Highlights: Methane from different sources was simultaneously measured for tritium and 14 C. Ultra-low-background detectors allow for significantly reduced sample size. Dual-isotope measurements are well-suited for samples with elevated tritium levels. Low-level tritium samples are better suited for commercial separation and counting.